Single earners and carers during lockdown: everyday challenges faced by Finnish single mothers during the COVID-19 pandemic - Salin Milla; Hakovirta Mia; Kaittila Anniina; Raivio Johanna (EMERALD GROUP PUBLISHING LTD, 2025)
PurposeThis article analyzes the challenges Finnish single mothers experienced in their everyday lives during the COVID-19 pandemic. In studies on challenges to family life during COVID-19 lockdowns, single-parent families remain a largely understudied group.Design/methodology/approachThe authors apply triple bind theory and ask how did Finnish single mothers manage the interplay between inadequate resources, inadequate employment, and inadequate policies during lockdown in spring 2020? These data come from an online survey including both qualitative and quantitative questions which was conducted between April and May 2020 to gather Finnish families' experiences during lockdown. This analysis is based on the qualitative part of the survey.FindingsThis study's results show that lockdown created new inadequacies while also enhancing some old inadequacies in the lives of Finnish single mothers. During lockdown, single mothers faced policy- and resource-disappearances; accordingly, they lost their ability to do paid work normally. Furthermore, these disappearances endangered the well-being of some single mothers and their families.Originality/valueThis article contributes to the wider understanding of everyday lives of single mothers and the challenges COVID-19 pandemic created. Moreover, this study provides knowledge on the applicability of the triple bind theory when studying the everyday lives of single mothers.